Aquaporins: New players in breast cancer progression and treatment response - Charlestin, Verodia; Fulkerson, Daniel; Arias Matus, Carlos E.; Walker, Zachary T.; Carthy, Kevin; Littlepage, Laurie E. (Frontiers in Oncology, 2022)
Aquaporins (AQPs) are a family of small transmembrane proteins that selectively transport water and other small molecules and ions following an osmotic gradient across cell plasma membranes. Recent evidence supports key roles for AQPs in cell migration, adhesion, proliferation, and cancer progression through AQPs’ function in transport of water, glycerol, and other small molecules. In this review, we provide a general overview of AQP structure, function, and expression patterns. We then focus on the role of AQPs in breast cancer and in the tumor microenvironment. We also discuss how AQPs contribute to response to cancer treatment, existing AQP inhibitors, and how AQPs could serve as novel predictive biomarkers of therapy response in breast cancer.